Factors affecting mortality in major trauma patients in Trinidad and Tobago – A view from the developing world. (July 2020) - Varachhia, Saleem; Ramcharitar Maharaj, Vidya; Paul, Joanne F; Robertson, Paula; Nunes, Paula; Sammy, Ian
Introduction: There are few data on major trauma in the developing world. This study investigated the characteristics and outcomes of seriously injured patients in Trinidad and Tobago, using Trauma and Injury Severity Score (TRISS) methodology. We also aimed to assess the predictive accuracy of the TRISS model in patients in Trinidad and Tobago. Methods: Retrospective data from major trauma patients attending the Emergency Department of a tertiary hospital in Trinidad between 2010 and 2014 were analysed. Patients ≥18 years having an Injury Severity Score >15 were included. The impact of age, gender, comorbidities, mechanisms and patterns of injury on mortality was investigated. Using TRISS methodology, predicted mortality was calculated and compared to actual mortality. Results: Of 323 patients analysed, 284 were male and 24 were aged ≥65 years. The commonest injury mechanisms in younger people were motor vehicle accidents (34.1%) and stabbings (30.8%) compared to falls (66.7%) and motor vehicle accidents (20.8%) in people aged ≥65 years. The commonest areas injured were the chest in younger patients (81.9%) and the head and neck in patients aged ≥65 years (58.3%). Women's mortality rates were similar to men (RR 1.8; 95% CI 0.7–4.9). Mortality was higher with age ≥65 years (RR 7.0; 95% CI 3.1–15.9), blunt trauma (RR 7.6; 95% CI 1.8–32.4) and Charlson Comorbidity Index of 1 or more (RR 3.2; 95% CI 1.3–8.0). The TRISS model performed well at lower ISS scores and was excellent at predicting survival (discrimination statistic 0.94). Conclusion: Multiple factors influence mortality in major trauma patients in Trinidad and Tobago, including age, co-morbidities and injury mechanism. TRISS methodology accurately predicted survival in this population but was better at predicting mortality in patients with lower Injury Severity Score.